Tracing the trajectories of SARS-CoV-2 variants of concern between December 2020 and September 2021 in the Canary Islands (Spain) - Ciuffreda, Laura; González-Montelongo, Rafaela; Alcoba-Florez, Julia; García-Martínez de Artola, Diego; Gil-Campesino, Helena; Rodríguez-Pérez, Héctor; Íñigo-Campos, Antonio; De Miguel-Martínez, Isabel; Tosco-Nuñez, Tomás; Díez-Gil, Oscar; Valenzuela-Fernández, Agustín; Lorenzo-Salazar, José M.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Several variants of concern (VOCs) explain most of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) epidemic waves in Europe. We aimed to dissect the spread of the SARS-CoV-2 VOCs in the Canary Islands (Spain) between December 2020 and September 2021 at a micro-geographical level. We sequenced the viral genome of 8,224 respiratory samples collected in the archipelago. We observed that Alpha (B.1.1.7) and Delta (B.1.617.2 and sub-lineages) were ubiquitously present in the islands, while Beta (B.1.351) and Gamma (P.1/P.1.1) had a heterogeneous distribution and were responsible for fewer and more controlled outbreaks. This work represents the largest effort for viral genomic surveillance in the Canary Islands so far, helping the public health bodies in decision-making throughout the pandemic.